PENINGKATAN KEPEDULIAN LINGKUNGAN MASYARAKAT DESA BOJONG KAMAL MELALUI EDUKASI DAN PELATIHAN PEMBUATAN LILIN AROMATERAPI DARI LIMBAH MINYAK JELANTAH - Saadah, Najmatus; Cindy Fatikasari; Saffanah Latifiani Adam; Dasumiati Dasumiati (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
This Community Service Program (KKN) aims to increase the environmental awareness and knowledge of the residents of Bojong Kamal Village regarding waste cooking oil management through education and aromatherapy candle-making training. The program was initiated due to the community’s low awareness of the environmental hazards caused by improper disposal of used cooking oil, which can pollute water and soil. The implementation methods included initial observation, socialization, hands-on training in producing aromatherapy candles, and evaluation of participants’ understanding and skills. The results indicate a significant improvement in public awareness and knowledge of the negative impacts of cooking oil waste, as well as the development of new skills to transform waste into economically valuable products. This activity not only fosters environmental responsibility but also encourages innovation in creating environmentally friendly products that benefit the local community.